Applying Nutrient Expert system for rational fertilisation to tea (Camellia sinensis) reduces environmental risks and increases economic benefits. (10th July 2021) - Tang, Sheng; Zheng, Nan; Ma, Qingxu; Zhou, Jingjie; Sun, Tao; Zhang, Xin; Wu, Lianghuan
Abstract: The overuse and unbalanced application of fertilisers have become common practices in the modern world, causing serious environmental problems and restricting tea growth and quality. Therefore, a scientific and rational fertilisation recommendation method should be developed to solve these problems. In this study, fertilisation datasets collected from field experiments (n = 548) in tea-producing areas (n = 21) from 2016 to 2020 were used to build (n = 492) and validate (n = 56) the Nutrient Expert (NE) system for tea. The field validation results indicated that the NE system significantly increased tea yield, quality, economic benefits, and nitrogen (N) use efficiency, as well as decreased greenhouse gas (GHG) emissions. Compared with current farmers' practice (FP), NE reduced fertiliser-sourced N, phosphorus (P), and potassium (K) application rates by 28%, 25%, and 20%, respectively. On average, NE increased tea yields by 14.0% and 9.3% relative to FP and soil testing (ST). The total concentration of free amino acids, which is one of the most important indexes of green tea quality, were highest in the NE treatment. The net economic benefits of NE increased by 20.0% and 12.6% relative to FP and ST. NE also increased the N utilisation efficiency of tea shoots by 87.0% and 85.3% compared to FP and ST, respectively. Moreover, NE reduced total GHG emissions by 27.7% and 9.6% compared to FP and ST. These results suggest that fertiliser recommendations based on the NE system can increase economic benefits and reduce environmental risks by avoiding excessive fertilisation to maintain sustainable agriculture. Graphical abstract: Graphical abstract. Schematic representation of the NE system for tea. The blue boxes and arrows indicate reductions, whereas those in red indicate increments. The green boxes indicate the parameters of the NE system for tea. Image 1 Highlights: Nutrient expert system of tea constructed based on YR and AE relationship. NE system increased tea yield and quality in spring, summer, and autumn. NE increased economic benefit for farmers. NE system decreased GHG emissions compared with FP and ST.